PERBANDINGAN TIPE PREFERENSI PERSONALITI ANTARA MAHASISWA AKUNTANSI DENGAN MAHASISWA MANAJEMEN, ILMU EKONOMI STUDI PEMBANGUNAN, ILMU ADMINISTRASI BISNIS, DAN TEKNIK INDUSTRI - Haritstya Afriandhi; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
This study aimed to get empirical evidence about type of personality preferences comparison between accounting students with student management, development studies economics, business administration science, and industrial engineering to enter the accounting profession. The sample in this study were taken using random sampling method of data collection with the criteria of the respondents had been studying the course at least 3 years or at the level of the semester 7. The data obtained is then analyzed using cross tabulation analysis and chi-square test different. The results showed that there was no significant difference between accounting students with other majors as a whole through the chi-square test different. But when compared to the one by one through the cross tabulation analysis, only the management students who considered suitable to enter the accounting profession. Most students of accounting and management have the type of personality preferences sensing-thinking with their respective percentages of 58% and 54%. Individuals who have the type of personality preferences sensing-thinking is judged to have an objective assessment, standard priority than personal values, process-oriented, and make decisions based on logical considerations. This is consistent with one of the five basic principles of the accounting profession is objectivity.